Flood Risk Analysis for the Construction of the Patimban Port Access Toll Road - Mulyawati, Fauzia; Abdullah Dwi Noviantoro, Agung; Savitri Nurvita, Rully (UKaRsT, 2024)
In recent decades, the risk of flooding in the Cipunagara River area has increased due to global climate change causing more extreme rainfall patterns. The planned construction of the Patimban Port Access Toll Road has a strategic role in supporting national logistics connectivity. However, the geographical location of the planned toll road in the lowlands near the Cipunagara River poses a significant risk to the sustainability of the infrastructure. This study aims to analyze the risk of flooding in the Cipunagara River and its impact on the design of the toll road. Hydrological analysis was carried out using rainfall data from eight observation stations for the period 2012–2021. Analysis of frequency distribution, rainfall intensity and the Soil Conservation Services (SCS) Unit Hydrograph method was carried out to calculate peak flood discharge. Modeling was carried out using Surface Water Modeling System (SMS) software. The results of the study indicate that the Cipunagara River Basin (DAS) has high rainfall variability with the potential for extreme rainfall in large return periods. The peak discharge of the 100-year return period is 1003.582 m³/second, indicating the risk of extreme flooding because it exceeds the river capacity of 309.31 m³/second. The results of flood modeling show that the flood water level in the 100-year return period reaches +8,908 meters, which confirms the need for a minimum toll road infrastructure elevation of +9,908 meters to meet the vertical clearance standard. These findings provide a significant contribution to the planning of toll road infrastructure that is more resilient to flood risks, supports operational sustainability, and reduces potential economic losses.